A complex gene regulatory architecture underlies the development and evolution of cuticle morphology in Drosophila. - Kittelmann, S.; Preger-Ben Noon, E.; McGregor, A.P.; Frankel, N. (Current Opinion in Genetics and Development, 2021)
The cuticle of insects is decorated with non-sensory hairs called trichomes. A few Drosophila species independently lost most of the dorso-lateral trichomes on first instar larvae. Genetic experiments revealed that this naked cuticle phenotype was caused by the evolution of enhancer function at the ovo/shavenbaby (ovo/svb) locus. Here we explore how this discovery catalyzed major new insights into morphological evolution in different developmental contexts, enhancer pleiotropy in gene regulation and the functionality and evolution of the Svb gene regulatory network (GRN). Taken together this highlights the importance of understanding the architecture and evolution of gene regulatory networks in detail and the great potential for further study of the Svb GRN.